Chemical and biological assays of Brassica rapa subsp. chinensis (L.) Hanelt - Rahman, Mohammad S; Jahan, Nushrat; Khatun, Mahbuba; Rashid, Mohammad A (Bangladesh Journal of Botany, 2018)
Bangladesh is in the tropical zone blessed with many plants and people of this country are dependent on them to a greater extent for foods and medicines. Brassica is a broad genus and encompasses a lot of herbs. Among these, Brassica rapa subsp. chinensis (L.) Hanelt (Family-Brassicaceae) is famous in Bangladesh as vegetables. In order to explore the healing abilities of B. rapa subsp. chinensis, different chemical and biological assays have been conducted. Initially, the sun-dried powdered herb was extracted well with methanol and then partitioned with petroleum ether, carbon tetrachloride, chloroform and aqueous soluble fractions. All these extractives were subjected to brine shrimp lethality, free radical scavenging, phenolic content determination and antimicrobial assays. B. rapa subsp. chinensis exhibited various responses in the conducted assays depending on the extractives. These studies revealed the facts to consider this plant with medicinal qualities in addition to its general identity as vegetables.